Pertanggungjawaban Pidana Rumah Sakit Bagi Dokter Atau Tenaga Kesehatannya Melakukan Malpraktik - Priantara, I Nyoman Agus Adi; Darmadi, A.A Ngurah Oka Yudistira (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 12 (2020), 2020)
The study is to determine the meaning of malpractice and the elements that can be categorized as fulfilling the elements of malpractice and to find out the form of responsibility on the part of the hospital due to a doctor or health worker who commits malpractice. This research method uses normative legal research and uses research methods on legal principles. The results of the study show that in cases of medical malpractice it is not only doctors or health workers who can be responsible for the malpractice, patients or health service recipients can also hold the hospital or corporations accountable. Hospitals as corporations can be used as legal subjects because legal entities also act as supporters of rights and obligations. The hospital as an organization that carries out tasks in the health sector is responsible for everything that happens in the hospital, which is generally borne by the management or director of the hospital concerned.   Key words : Criminal Liability, Hospital, Doctor or Health Worker Malpractice